Spatial navigation entropy suggests allocentric dysfunction in PPPD - Faúndez, Felipe; Arévalo-Romero, Camilo; Villarroel, Karen; Lavín, Claudio; Alarcón, Kevin; Vial, Gustavo; Artus, Francisco; Billeke, Pablo; Delano, Paul H.; Breinbauer, Hayo A. (Frontiers in Neurology, 2025)
IntroductionPersistent postural-perceptual dizziness (PPPD) is a common chronic dizziness disorder with an unclear pathophysiology. It is hypothesized that PPPD may involve functional dysfunction of the construction of inner cognitive maps, leading to disrupted spatial cognition processes as a core feature. The present studies attempt to unravel the neural mechanisms that underlie spatial navigation in PPPD.MethodsFifty-two participants completed the study: 19 PPPD patients, 20 control subjects with vestibular disorders but without PPPD (with comparable peripheral vestibular function to the PPPD group, and 13 healthy volunteers). All underwent a virtual Morris Water Maze (vMWM) task in both, non-immersive (NI) and virtual reality (VR) modalities, assessing spatial navigation performance, gaze behavior, and head kinematics.ResultsPPPD patients exhibited significantly worse navigation performance than both control groups across all metrics, with greater impairments in predominantly allocentric tasks. They also showed increased exploratory gaze behavior, unaffected by NI vs. VR modality or task condition. Head kinematics did not significantly differ between the three groups, though a non-significant trend indicated reduced head movement in both PPPD and vestibular controls. VR intolerance was highest in PPPD patients, followed by vestibular controls, with healthy volunteers showing the lowest discomfort.DiscussionOur findings suggest that PPPD involves deficits in allocentric spatial navigation, likely due to predictive coding errors and impaired internal model updating, rather than sensory input dysfunction. Increased gaze scanning may reflect compensatory mechanisms for spatial uncertainty. Notably, VR immersion did not alter navigation performance, suggesting visuo-vestibular conflict is not the primary driver of PPPD-related spatial deficits. These findings offer new insights into PPPD as a disorder of spatial cognition, opening avenues for novel diagnostic and therapeutic approaches.